Groundwater rejuvenation in parts of India influenced by water-policy change implementation - Bhanja, S.; Mukherjee, Abhijit; Rodell, M.; Wada, Y.; Chattopadhyay, S.; Velicogna, I.; Pangaluru, K.; Famiglietti, J. (Nature Publishing Group, 2017)
The dwindling groundwater resource of India, supporting almost one fifth of the global population and also the largest groundwater user, has been of great concern in recent years. However, in contrary to the well documented Indian groundwater depletion due to rapid and unmanaged groundwater withdrawal, here for the first time, we report regional-scale groundwater storage (GWS) replenishment through long-term (1996-2014, using more than 19000 observation locations) in situ and decadal (2003-2014) satellite-based groundwater storage measurements in western and southern parts of India. In parts of western and southern India, in situ GWS (GWS obs ) has been decreasing at the rate of -5.81 ± 0.38 km 3 /year (in 1996-2001) and -0.92 ± 0.12 km 3 /year (in 1996-2002), and reversed to replenish at the rate of 2.04 ± 0.20 km 3 /year (in 2002-2014) and 0.76 ± 0.08 km 3 /year (in 2003-2014), respectively. Here, using statistical analyses and simulation results of groundwater management policy change effect on groundwater storage in western and southern India, we show that paradigm shift in Indian groundwater withdrawal and management policies for sustainable water utilization appear to have started replenishing the aquifers in western and southern parts of India.